Recent velocity field in western Anatolia from continuous GPS data - Kaynarca, Tayfun. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2019., 2019)
Aegean Region is one of the most deforming parts of Alpine-Himalayan orogenic belt. The region is intensely under pure shear stress which is caused by an internally deforming counter-clock rotation of the Anatolian plate relative to Eurasian plate. The counter-clockwise motion caused by the compression of the Arabian plate through Anatolian plate eventuate in north-south extension and formation of east-west trending active grabens. Many seismological studies were carried out in Western Anatolia and its surroundings due to remarkable seismic activity in the area. In this study, GPS data from 16 of CORS-TR stations which measured in 2015, 2016, 2017 and 2018 were used by considering the seasonal eﬀects. The obtained velocities of selected CORS-TR stations were combined with the velocity ﬁelds of Reilinger et al., (2006) and Aktu˘g et al., (2009) for better understanding of the dynamic mechanism of the region. 14 mutual IGS stations in the studies were utilized for the transformation process. Combined velocity values vary between 10.66 ± 1.22 mm/yr and 32.71 ± 0.54 mm/yr. The obtained velocity ﬁeld demonstrates that Western Anatolia is characterized by predominantly north-south extension and experiencing rapid internal deformation. Western Anatolia’s internal mechanism supports graben formation in the east-west direction and results are consistent with the characteristics of the Western Anatolia extensional mechanism.
Keywords: Earthquakes -- Turkey.; Global Positioning system -- Turkey.; Seismology -- Data processing.